2021
DOI: 10.1097/qad.0000000000002817
|View full text |Cite
|
Sign up to set email alerts
|

Using phylogenetic surveillance and epidemiological data to understand the HIV-1 transmission dynamics in French Guiana

Abstract: Objective: The aim of this study was to understand the transmission dynamics of the HIV-1 subtype B epidemic in French Guiana and the factors that shaped the expansion of major phylogenetic transmission clusters.Design: HIV-1 subtype B pol sequences with associated epidemiological data obtained from 703 treatment-naive patients living in French Guiana between 2006 and 2012, which correspond to 91% of all HIV cases diagnosed in that period, were employed in this study.Methods: Maximum likelihood and Bayesian me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…We have shown that in French Guiana Bcar lineages are predominant over B pandemic lineages (25,26). In Brazil, B pandemic lineages (and to a far lesser degree F) largely predominate; the 3 Brazilian states that have the greatest proportion of Bcar lineages are Maranhao, Roraima, and Amazonas (27), areas that are notoriously linked to gold mining and where many garimpeiros come from, notably, for French Guiana, Maranhao.…”
Section: Results Of the Review Of Available Information Hiv/aidsmentioning
confidence: 88%
“…We have shown that in French Guiana Bcar lineages are predominant over B pandemic lineages (25,26). In Brazil, B pandemic lineages (and to a far lesser degree F) largely predominate; the 3 Brazilian states that have the greatest proportion of Bcar lineages are Maranhao, Roraima, and Amazonas (27), areas that are notoriously linked to gold mining and where many garimpeiros come from, notably, for French Guiana, Maranhao.…”
Section: Results Of the Review Of Available Information Hiv/aidsmentioning
confidence: 88%
“…While 29% of the total population and nearly half of adults are foreigners, for persons living with the Human Immunodeficiency Virus (HIV), 80% are foreigners ( 3 ). Although many immigrants with HIV come from HIV endemic countries, we have shown that over half acquire the infection early after arrival in French Guiana, presumably because of enhanced sexual vulnerability linked to social precariousness ( 4 , 5 ). In this context, the transmission mode of HIV is by far mostly heterosexual, with a balanced number of males and females.…”
Section: Introductionmentioning
confidence: 89%
“…Innovative research approaches which can be utilized to generate nuanced insights and inform targeted prevention strategies include phylogenetic and phylodynamic analysis of HIV sequences to study phylogenetic clustering in migrant communities, providing insights into when and where transmissions occurred, but so far, these efforts were mostly limited to labour migrants [82,83]. Rapid, portable and relatively cheap genetic sequencing technologies (i.e.…”
Section: Harnessing Momentum To Achieve Hiv Equitymentioning
confidence: 99%